Agricultural Growth Corridors - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2016)
This document contains the finalized study on “Agricultural Growth Corridors: mapping potential research gaps on impact, implementation and institutions” together with the ISPC commentary. The study aims to inform policy-makers and researchers about how development corridors might bring about changes in patterns of agriculture and consequently influence research needs.